EU Institutional Reform: Evidence on Globalization and International Cooperation - Baldwin, Richard (American Economic Review, 2008)
If the received wisdom is right, the EU's rapid economic integration should have been asso? ciated with a transfer of economic policy sov? ereignty to the supranational level. This paper marshals several strands of evidence in support the received wisdom, although the relationship in the EU is clearly two-way. Economic inte? gration makes governments more interested in international cooperation, but the institutional reforms that facilitate such cooperation also facilitate deeper economic integration.